Resurfacing Hip Replacement and Cemented Total Hip Replacement have Equivalent Outcome at One Year in a Disease Matched Population: A Case-Control Study of Patient Reported Outcome Measures. Issue 4 (July 2013) - Ray, Robbie; Goudie, Ewan B.; Jenkins, Paul; Gaston, Paul
Resurfacing hip replacement has demonstrated good survival and outcomes for cohorts of younger male patients, but few controlled studies exist. In this study we compared patient reported outcome measures and satisfaction scores at one year following resurfacing hip replacement in 69 male patients with two control groups of equal numbers undergoing cemented total hip replacement: aged-matched patients and disease matched patients. At one year we found no difference in improvement in patient reported outcome measures between patients undergoing resurfacing hip replacement and disease matched patients, whereas patients undergoing resurfacing hip replacement had a statistically significant improvement in Oxford Hip Score compared to the age-matched controls (p<0.047) although this was below the minimally clinically detectable difference. Resurfacing hip replacement and total hip replacement both confer increase in patient reported outcome scores and high patient satisfaction at one year. The results of this study will allow better counselling of patients and help inform treatment decisions.